What happens when software developers are (un)happy - Graziotin, Daniel; Fagerholm, Fabian; Wang, Xiaofeng; Abrahamsson, Pekka (The Journal of systems and software, 2018)
•Consequences of happiness and unhappiness among software developers detailed.•More positive consequences of happiness are experienced related to the self.•More negative consequences of unhappiness are experienced for external factors.•Results based on qualitative analysis of more than 300 developers’ experiences.•Category scheme of consequences usable for further studies and as guidelines. The growing literature on affect among software developers mostly reports on the linkage between happiness, software quality, and developer productivity. Understanding happiness and unhappiness in all its components – positive and negative emotions and moods – is an attractive and important endeavor. Scholars in industrial and organizational psychology have suggested that understanding happiness and unhappiness could lead to cost-effective ways of enhancing working conditions, job performance, and to limiting the occurrence of psychological disorders. Our comprehension of the consequences of (un)happiness among developers is still too shallow, being mainly expressed in terms of development productivity and software quality. In this paper, we study what happens when developers are happy and unhappy while developing software. Qualitative data analysis of responses given by 317 questionnaire participants identified 42 consequences of unhappiness and 32 of happiness. We found consequences of happiness and unhappiness that are beneficial and detrimental for developers’ mental well-being, the software development process, and the produced artifacts. Our classification scheme, available as open data enables new happiness research opportunities of cause-effect type, and it can act as a guideline for practitioners for identifying damaging effects of unhappiness and for fostering happiness on the job.